2017
DOI: 10.1164/rccm.201612-2414oc
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Determinants of Bronchopulmonary Dysplasia and Late Respiratory Disease in Preterm Infants

Abstract: We conclude that maternal smoking and hypertension increase the odds for developing BPD after preterm birth, and that maternal smoking is strongly associated with increased odds for late respiratory morbidities during early childhood. These findings suggest that in addition to the BPD diagnosis at 36 weeks, other factors modulate late respiratory outcomes during childhood. We speculate that measures to reduce maternal smoking not only will lower the risk for preterm birth but also will improve late respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
137
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 51 publications
1
137
1
5
Order By: Relevance
“…In VLBW infants, postnatal growth rather than appropriateness of weight for gestational age determines later neurodevelopmental outcome (Latal‐Hajnal et al, ). Adverse prenatal and postnatal influences can alter fetal and postnatal growth predisposing to chronic disease in adults (Stick et al, ; Sly and Bush, ; Morrow et al, ). Rodent models have been used to study long‐term risks associated with prematurity, as lung development in newborn mice at birth is comparable to 26 weeks gestational age human infant and much of the alveolarization of the rodent lung occurs in the first two postnatal weeks (Burri, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In VLBW infants, postnatal growth rather than appropriateness of weight for gestational age determines later neurodevelopmental outcome (Latal‐Hajnal et al, ). Adverse prenatal and postnatal influences can alter fetal and postnatal growth predisposing to chronic disease in adults (Stick et al, ; Sly and Bush, ; Morrow et al, ). Rodent models have been used to study long‐term risks associated with prematurity, as lung development in newborn mice at birth is comparable to 26 weeks gestational age human infant and much of the alveolarization of the rodent lung occurs in the first two postnatal weeks (Burri, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that lead to preterm birth by themselves alter fetal lung development, making it difficult to separate the neonatal consequences of such factors from prematurity. Maternal smoking (Stick et al, ; Morrow et al, ) and chorioamnionitis (Jobe, ) adversely effect lung development and increase the risk of chronic lung disease in infants and children. Air pollution and chemical exposure both before and after birth are significantly associated with asthma, chronic lung disease, and COPD in later life (Hsu et al, ; Bose et al, ).…”
mentioning
confidence: 99%
“…Several prenatal (Morrow et al. ), postnatal (Jobe ), and genetic factors (Bhandari and Gruen ) act on the immature lung leading to development of BPD. Multifactorial origin of the disease makes it especially difficult to treat these infants, with no specific therapies in sight.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchopulmonary dysplasia is the most common form of chronic lung disease following premature birth, especially in extremely low-birth-weight (ELBW) infants. Several prenatal (Morrow et al 2017), postnatal (Jobe 2011), and genetic factors (Bhandari and Gruen 2006) act on the immature lung leading to development of BPD. Multifactorial origin of the disease makes it especially difficult to treat these infants, with no specific therapies in sight.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians and researchers emphasised the need to consider lung function trajectories in future asthma guidelines to better monitor lung growth throughout life based on two papers recently published in the Lancet Respiratory Medicine [19,20]. Regarding bronchopulmonary dysplasia (BPD), recent studies showed that intrauterine growth restriction, maternal smoking and pre-existing hypertension were associated with increased risk of BPD [21] and that BPD impairs cognitive development and quality of life in infants born extremely preterm [22]. Concerning the early-life origins of respiratory disorders, two cohorts showed that school-aged asthma was influenced by earlier lower respiratory tract infections or asthma symptoms, but not by upper respiratory tract infections [23,24].…”
Section: Assembly 7: Paediatrics (Maribel Casas)mentioning
confidence: 99%